Exploratory analysis of preventable first day mortality in Colombia (2016)
Objective. The goal of this study was to inform public health policy which can reduce Colombia's estimated infant mortality rate (IMR), 17.78 deaths for 1000 live births (2011), by lowering preventable first day mortality (PFDM). Study design This study combined a time series analysis, using a linear regression method, for the period 2001–2012 with a cross-sectional analysis, using odds ratios and bi-variate methods, for the year 2012 to study first day mortality (FDM) and PFDM classified by biological, socio-economic, and medical correlates. Methods The study examined the trends for 2001–2012 in Colombia's infant mortality rate per 1000, and in the relative significance of PFDM by cause. It established the relative odds of PFDM for 2012 by major risk categories, defined by birthweight and gestational age, and within those by biological, sociodemographic risk factors or groups and by potential access to and use of care. Then, the study established the major causes of PFDM within major risk categories and groups.